(untitled) (European Journal of Pure and Applied Mathematics, 2012)
The m-spotty byte error control codes can correct or detectmultiple spotty byte errors that are distributed in multiplebytes. These codes are successfully applied to computer memorysystems that use RAM chips with b-bit Input/Output data whenhigh-energy particles strike a particular RAM chips. In thispaper, we derive a MacWilliams type identity for m-spotty Hammingweight enumerator over the ring F_2+vF_2 withv^2=v.